1978
DOI: 10.1288/00005537-197810000-00001
|View full text |Cite
|
Sign up to set email alerts
|

A one‐stage combined approach for the management of large cerebellopontine angle tumors

Abstract: This paper reviews 180 cerebellopontine angle lesions in regard to results and complications of the surgical management with special emphasis on the diagnosis, surgical removal, and results in 60 large (4 cm. or greater) tumors of the CPA. The authors conclude that in their experience a one-stage combined translabyrinthine-suboccipital approach, which is explained in detail, is the procedure of choice in dealing with large tumors of the CPA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1
1

Year Published

1981
1981
1992
1992

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 7 publications
1
15
1
1
Order By: Relevance
“…For instance, some investigators reported that the rate was 92% or higher in patients with small or mediumsized tumors. Among patients with large tu mors, a facial nerve preservation rate of 20% was reported by King [8], 67% by Glasscock et al [2], and 77% by Tos and Thomson [11]. Our result (69%), shown in table V, can be said to be similar to the results in the abovementioned reports.…”
Section: Rate O F Facial Nerve Preservationsupporting
confidence: 89%
See 1 more Smart Citation
“…For instance, some investigators reported that the rate was 92% or higher in patients with small or mediumsized tumors. Among patients with large tu mors, a facial nerve preservation rate of 20% was reported by King [8], 67% by Glasscock et al [2], and 77% by Tos and Thomson [11]. Our result (69%), shown in table V, can be said to be similar to the results in the abovementioned reports.…”
Section: Rate O F Facial Nerve Preservationsupporting
confidence: 89%
“…If only the rate of total removal is considered, there are reports stating such fa vorable figures as 98% [2,11], while Palva and Troupp [10] reported a total removal rate of 72% by the TL method. Our finding of 81 % lies between the above percentages.…”
Section: Mortality and Tumor Removalmentioning
confidence: 99%
“…In a study in which the suboccipital approach was combined with the translabyrinthine approach, the anatom ical facial nerve preservation rate was found to be 84% [2], Large discrepancies are seen in the results obtained by different investiga tors on the functional preservation rate, es pecially in patients with large tumors, for whom rates of 14.5 [6], 77 [8], and 75-92% [10] have been reported. Although func tional preservation is more important than anatomical preservation, there are few de tailed reports on this subject.…”
Section: Discussionmentioning
confidence: 99%
“…3B), ready for use at the time of closure. 3. A large C-shaped postauricular incision is made, the belly of the "C" being at least 6 cm posterior to the postauricular crease (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The reported incidence of CSF leaks with this technique is 4 to 18%. [1][2][3][4] In an effort to reduce the incidence of such leaks, House5 used the temporalis muscle to close the dural opening. Nevertheless, in his first series of cases there was still a frequent occurrence of postoperative CSF leak.…”
Section: Prevention Of Cerebrospinal Fluidmentioning
confidence: 99%